Double perovskite cathodes for proton-conducting ceramic fuel cells: are they triple mixed ionic electronic conductors?. Issue 1 (31st December 2017) - Téllez Lozano, Helena; Druce, John; Cooper, Samuel J.; Kilner, John A.
Abstract: 18 O and 2 H diffusion has been investigated at a temperature of 300 °C in the double perovskite material PrBaCo2 O5+ δ (PBCO) in flowing air containing 200 mbar of 2 H2 16 O. Secondary ion mass spectrometry (SIMS) depth profiling of exchanged ceramics has shown PBCO still retains significant oxygen diffusivity (~1.3 × 10 −11 cm 2 s −1 ) at this temperature and that the presence of water ( 2 H2 16 O), gives rise to an enhancement of the surface exchange rate over that in pure oxygen by a factor of ~3. The 2 H distribution, as inferred from the 2 H2 16 O − SIMS signal, shows an apparent depth profile which could be interpreted as 2 H diffusion. However, examination of the 3-D distribution of the signal shows it to be nonhomogeneous and probably related to the presence of hydrated layers in the interior walls of pores and is not due to proton diffusion. This suggests that PBCO acts mainly as an oxygen ion mixed conductor when used in PCFC devices, although the presence of a small amount of protonic conductivity cannot be discounted in these materials. Abstract :